Decision and Coordination Strategies for RoboCup Rescue Agents - Nanjanath, Maitreyi; Erlandson, Alexander J.; Andrist, Sean; Ragipindi, Aravind; Mohammed, Abdul A.; Sharma, Ankur S.; Gini, Maria (Second International Conference on Simulation, Modeling, and Programming for Autonomous Robots (SIMPAR ’10), 2010)
We describe the decision processes of agents in the Robocup Rescue Agent Simulation. Agents have to rescue civilians trapped in buildings and extinguish fires in a city which has been struck by an earthquake. Lack of information and limited communications hamper the rescue process. We examine how effective our strategies and algorithms are and compare their performance against the baseline agents and agents which competed in last year’s competition.